Penal Mediation in Settlement of Disputes of Hurt Dayak Ngaju Traditional Law - Dody Heryanto; I Nyoman Nurjaya; Prija Djatmika; Hanif Nur Widhiyanti (Budapest International Research and Critics University, 2021)
Penal mediation in the settlement of disputes regarding insults to the Dayak tribe under the customary law of the Ngaju Dayak as stipulated in the Tumbang Anoi Agreement of 1894. Meaning Penal mediation in the settlement of criminal cases of insulting the Dayak Ngaju customary law are (1) The implementation of penal mediation in the settlement of disputes over insulting the Dayak Ngaju customs is an effort to preserve culture through customary law owned by the Dayak tribe as stipulated in the Tumbang Anoi agreement of 1894, as for the procession settlement of insult disputes, namely by means of mediation between the perpetrator and the victim after it is decided by the damangan and (2) the decision by the customary institution addressed to the perpetrator can be in the form of Tandahan Randah, article 50 Singer Tandahan Randah (customary fines, haphazard accusations) is prohibited from insulting, demeaning , vilify or slander others; Sala Basa, article 63 Singer Karak Sirat Dahiang (traditional fines for destroying a good sirat or self-concept), are prohibited from mocking or destroying people's foreheads, and making people's hearts unhappy; Kasukup Singer Belom Bahadat, Article 96 Kasukup Singer Belom Bahadat (complement of customary fines for living with decency or ethics or high morals), belom bahadat is a principle of life for the indigenous Dayak Ngaju community which means living well in accordance with the rules and the truth. Penal mediation in the settlement of insult disputes through customary institutions is expected to be able to continue along with the times.